A cost-effectiveness analysis comparing two different strategies in advanced maternal age: Combined first-trimester screening and maternal blood cell-free DNA testing - Min Pan; Lv-Yin Huang; Li Zhen; Dong-Zhi Li (Taiwanese Journal of Obstetrics & Gynecology, 2018)
Objective: To estimate cost efficacy of first-trimester screening strategies based on nuchal translucency (NT) and maternal blood cell-free DNA (cfDNA) testing in women with advanced maternal age (AMA). Materials and methods: This was a retrospective population-based analysis of all pregnant women with AMA booked for combined first-trimester screening (cFTS) in China over a 3-year period. The assumed screening strategies were the following: cFTS (Strategy 1), cfDNA testing as a first-tier investigation replacing biomarkers after NT measurement (Strategy 2), and cfDNA testing combined with dating ultrasound for all women (Strategy 3). The direct costs were compared between strategies. Results: Strategy 1 was completed in 6443 women with AMA. The respective detection rates were 94.5% and 90.9% for trisomies 21 and 18, with a total screen-positive rate of 13.5%. Such a policy resulted in 871 invasive tests and a total cost of $747,870 or a cost of $116 per person tested. Strategy 2 would result in a total cost of $1,812,570, or a cost of $281 per person tested, with increased detection rates for trisomies 21 and 18, and a decreased number of invasive tests compared with strategy 1. The total cost of Strategy 3 would be $1,675,430, or a cost of $260 per person tested with the least number of invasive tests. Conclusion: The cfDNA modalities have the advantages of higher detection rate for common trisomies and lower screening-positive rate. However, the cost of cfDNA testing needs to decrease significantly if it is to replace the current cFTS practice in a population of AMA on a purely cost effectiveness basis. Keywords: Cost-effectiveness, Nuchal translucency, Prenatal screening, Cell-free DNA, Advanced maternal age